Acoustic streaming induced by the non-periodic sound in a viscous medium - Perelomova, Anna (Archives of Acoustics, 2007)
Instantaneous radiation force of acoustic streaming in a thermoviscous fluid is the subjectof investigation. Dynamic equation governing the velocity of acoustic streaming is a result ofsplitting of the conservative differential equations in partial derivatives basing on the featuresof all possible types of a fluid motion. The procedure of deriving does not need averaging oversound period. It is shown that the radiation force consists of three parts, one correspondingto the classic result (while averaged over sound period), the second being a small negativeterm caused by diffraction, and the third one. This last term equals exactly zero for periodicsound (after averaging) and differs from zero for other types of sound. Sound itself mustsatisfy the well-known Khokhlov–Zabolotskaya–Kuznetsov equation describing the weaklydiffracting nonlinear acoustic beam propagating over viscous thermconducting fluid. The partsof radiation acoustic force, relating to the sound non-periodicity and diffraction, are discussedand illustrated.